DO STUDENTS EXPERIENCE FLOW CONDITIONS ONLINE? - Katrina A. Meyer; Stephanie J. Jones (Online Learning, 2013)
This study asked graduate students enrolled in higher education programs at two institutions to ascertain whether and to what extent they experienced nine flow-related conditions in two settings: online courses or surfing or gaming online. In both settings, flow was experienced “sometimes,” although no significant difference in mean frequency was found for the two settings. When asked for examples of flow, however, students gave more examples drawn from non-class-related activities (n = 35) than class activities (n = 3), including researching a number of topics related to health, travel, or shopping, or engaging with Facebook. Finally, students found that online class experiences “frequently” impacted their satisfaction with the course and three flow conditions were found to be correlated with course satisfaction at p ≤ 0.05: clear goals, concentration and focus, and a sense of personal control over activity.